Efektivitas Penerapan Sanksi Denda Terhadap Tindak Pidana Pelanggaran Lalu Lintas (Studi Kasus di Pengadilan Negeri Tanjungpandan) - Sari, Novita sari; Anwar, Reski; Huda, Muhamad Nurul (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
Abstract: This study examines the effectiveness of imposing fines as a sanction for traffic violations, with a case study in the Tanjungpandan District Court. The research aims to analyze whether fines serve as an effective deterrent to reduce traffic violations and improve road safety. Data were collected from court records, interviews with legal practitioners, and observations of traffic cases processed in court. The results show that while fines are a common and easily enforceable punishment, their deterrent effect remains limited. Many violators view fines as a minimal consequence and fail to alter their driving behavior significantly. Additionally, the research highlights several challenges in the consistent application of fines, including discrepancies in the fines imposed and the socio-economic factors influencing the violators’ ability to pay. The study concludes that while fines play a role in sanctioning traffic violations, supplementary measures, such as public awareness campaigns and stricter law enforcement, are needed to enhance their effectiveness in reducing violations. Keywords: Traffic Violations, Fines, Sanctions, Deterrent Effect, Law Enforcement.